Histone deacetylase 6 controls Notch3 trafficking and degradation in T-cell acute lymphoblastic leukemia cells - Pinazza, Marica (Oncogene, 2018)
Several studies have revealed that endosomal sorting controls the steady-state levels of Notch at the cell surface in normal cells and prevents its inappropriate activation in the absence of ligands. However, whether this highly dynamic physiologic process can be exploited to counteract dysregulated Notch signaling in cancer cells remains unknown. T-ALL is a malignancy characterized by aberrant Notch signaling, sustained by activating mutations in Notch1 as well as overexpression of Notch3, a Notch paralog physiologically subjected to lysosome-dependent degradation in human cancer cells. Here we show that treatment with the pan-HDAC inhibitor Trichostatin A (TSA) strongly decreases Notch3 full-length protein levels in T-ALL cell lines and primary human T-ALL cells xenografted in mice without substantially reducing NOTCH3 mRNA levels. Moreover, TSA markedly reduced the levels of Notch target genes, including pTα, CR2, and DTX-1, and induced apoptosis of T-ALL cells. We further observed that Notch3 was post-translationally regulated following TSA treatment, with reduced Notch3 surface levels and increased accumulation of Notch3 protein in the lysosomal compartment. Surface Notch3 levels were rescued by inhibition of dynein with ciliobrevin D. Pharmacologic studies with HDAC1, 6, and 8-specific inhibitors disclosed that these effects were largely due to inhibition of HDAC6 in T-ALL cells. HDAC6 silencing by specific shRNA was followed by reduced Notch3 expression and increased apoptosis of T-ALL cells. Finally, HDAC6 silencing impaired leukemia outgrowth in mice, associated with reduction of Notch3 full-length protein in vivo. These results connect HDAC6 activity to regulation of total and surface Notch3 levels and suggest HDAC6 as a potential novel therapeutic target to lower Notch signaling in T-ALL and other Notch3-addicted tumors.